1981
DOI: 10.1126/science.7302587
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Oocyte Number Following Prenatal Exposure to a Diet High in Galactose

Abstract: When pregnant rats were fed a 50 percent galactose diet there was a striking reduction in oocyte number in the offspring. The most prominent effects were noted after exposure to galactose during the premeiotic stages of oogenesis. Prenatal exposure to galactose or its metabolites may contribute to the premature ovarian failure characteristic of human galactosemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
2
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 9 publications
2
87
2
1
Order By: Relevance
“…The ovary has relatively abundant levels of three of the major enzymes involved in metabolism of galactose (galactokinase, galactose-1-phosphate uridyltransferase (GALT) and UDP-galactose-4-epimerase) [6]. This fact is thought to be causally related to the observation that women who have absent or low GALT activity have a propensity to develop premature ovarian failure and premature menopause [2,17]. However, since human diets contain foods high in lactose versus free galactose, our data are suggestive that women would not have the adverse effects observed in rodents that consume a high galactose diet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ovary has relatively abundant levels of three of the major enzymes involved in metabolism of galactose (galactokinase, galactose-1-phosphate uridyltransferase (GALT) and UDP-galactose-4-epimerase) [6]. This fact is thought to be causally related to the observation that women who have absent or low GALT activity have a propensity to develop premature ovarian failure and premature menopause [2,17]. However, since human diets contain foods high in lactose versus free galactose, our data are suggestive that women would not have the adverse effects observed in rodents that consume a high galactose diet.…”
Section: Discussionmentioning
confidence: 99%
“…Since the disaccharide lactose, consisting of one glucose molecule and one galactose molecule is the primary carbohydrate in milk, those who consume large quantities of dairy products in an effort to increase calcium intake for osteoporosis prevention ingest large quantities of lactose. The toxic effect of galactose or its metabolites within the ovary became apparent from the observations of extremely early ovarian failure (before age 30 years) in women with galactosemia (genetic absence of the enzyme galactose-1-phosphate uridyl transferase) [2]. Animal studies have suggested that diets rich in galactose produce insults that are at least somewhat comparable to those seen in galactosemics [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…POF or premature menopause is a syndrome clinically defined by failure of the ovary before the age of 40 yr (1). POF is a heterogeneous disorder with a multicausal pathogenesis, and chromosomal (2-9), genetic (4, 10 -12), enzymatic (13)(14), iatrogenic (15)(16)(17)(18)(19)(20), or infectious (21)(22) aberrations may all form the basis for the disappearance of ovarian follicles. These aberrations may influence the ovary at any stage of life, including the prepubertal, pubertal, or reproductive stages (23).…”
Section: Introductionmentioning
confidence: 99%